Структурно-функціональна семантика категорії “взаємодія” в педагогічній психології - Ковальчук, Зоряна (Видавництво Львівської політехніки, 2013)
Предлагаемая статья является философским, этимологическим, семантическим и лингвостилистическим анализом понятия “педагогическое взаимодействие”, что позволит углубить уровень понимания сущности его дефиниции для дальнейшего научного исследования. The article is a philosophical, etymological, semantic, lingual and stylistic analysis of the notion of “pedagogical interaction” that gives the possibility to raise understanding of its definition essence for further scientific researches.
Структурно-функциональная семантика категории “взаимодействие” в педагогической психологии
Structural and functional semantics of the category of interaction in pedagogical psychology
Keywords: семантика; взаимодействие; педагогическая психология; межличностный; учитель; ученик; semantics; interaction; pedagogical psychology; interpersonal; teacher; pupil